Răspuns
a) x + y + z + 24 = 48
x + y + z = 48 - 24
x + y + z = 24
_________________
15 + 2 z + 2 y + 2 x = 63
= 15 + 2 × ( x + y + z ) =
= 15 + 2 × 24 =
= 15 + 48 =
= 63
_________________________________________
b)
3 x + 3 y + 23 = 65
3 x + 3 y = 65 - 23
3 × ( x + y ) = 42
x + y = 42 : 3
x + y = 14
____________
2 x + 2 y + 27 = 55
= 2 × ( x + y ) + 27 =
= 2 × 14 + 27 =
= 28 + 27 =
= 55
________________________________
c)
x + 3 y + 2 z + 16 = 50
x + 3 y + 2 z = 50 - 16
x + 3 y + 2 z = 34
_______________
2 x + 6 y + 4 z + 12 = 80
= 2 × ( x + 3 y + 2 z ) + 12 =
= 2 × 34 + 12 =
= 68 + 12 =
= 80